A Case Series on Streptococcus agalactiae Infection in Llamas and Alpacas in a Semi-Intensive Breeding System in Southern Brazil - Vitor Eduardo Mamgue; Letícia Trevisan Gressler; Andriel Gustavo Felichak; Paulo Henrique Braz (Veterinary and Animal Science, 2025)
The South American Camelids (CSA), including llamas (Lama glama) and alpacas (Vicugna pacos), are primarily concentrated in the Andean countries of Argentina, Bolivia, Chile, and Peru, where they represent an important source of income for the local population. In Brazil, their captive breeding, although recent, has gained significant attention. These animals can act as potential carriers and transmitters of diseases, especially those with zoonotic potential. For many years, Streptococcus agalactiae was considered a strictly contagious bacterium among bovine herds. However, it has now been identified in various other animal species. This study aims to describe the clinical aspects of an outbreak of S. agalactiae in a herd of llamas and alpacas in southern Brazil. Two llamas and one alpaca presented chronic formation of encapsulated suppurative abscesses on the flank region. After conducting microbiological cultures, the pathogen was confirmed using MALDI-TOF MS. An antibiogram was performed, demonstrating antimicrobial sensitivity to most evaluated agents but indicating resistance to tetracycline, oxacillin, and orbifloxacin. The animals fully recovered after treatment with penicillin, with no recurrence of the infection. This study describes the first cases of S. agalactiae infection in llamas and alpacas in Brazil, highlighting the importance of further research on the health, breeding, and management of these animals.